MENINGKATKAN KEMAMPUAN MENENTUKAN LATAR CERPEN DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW SISWA KELAS IV SDN KLITIK 1 - Melik Budiarti; Dinar Widhi Paringga; Femma Aulia Putri Ibrahim; Fathia Salsabila (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve students' ability to recognize the setting of a short story through the implementation of the Jigsaw cooperative learning method. This research is based on initial observations indicating that students' literacy skills are still low, particularly in identifying elements of a short story's setting. The method used in this study is Classroom Action Research (CAR), which consists of two cycles encompassing four stages: planning, action, observation, and reflection. The subjects of this study were 18 fourth-grade students at SDN Klitik 1, Geneng District, Ngawi Regency. Data collection techniques were conducted through observation, interviews, written tests (pretest and posttest), and documentation. The results of the study indicate that the application of the Jigsaw method increased student engagement in the learning process and their understanding of the elements of a short story's setting. This is evident in the increase in students' average grades from the pre-action stage to the post-action stage, as well as the achievement of learning mastery in class. From these findings, it can be concluded that the Jigsaw cooperative learning model has proven effective in improving students' ability to identify the setting of a short story at the elementary school level.